What difference will it make? Impact of a Harris or Trump presidency on American foreign policy - Mark N. Katz (EconPol Forum, 2024)
If she is elected president, Kamala Harris is likely to continue President Joseph Biden's foreign policy, though her tone on the Middle East may differ somewhat from his. Just as Biden continued much of former President Donald Trump's foreign policy, a re-elected Trump is likely to continue much of Biden's. While Biden and Harris have been strong supporters of NATO, Trump has been more critical of it. Still, many see Trump's criticisms of NATO as being designed to push its European members to spend more on defense, not to pull the US out of the alliance. Trump has provided ample reason to doubt that he would be as supportive of Ukraine as Biden has been and Harris is likely to be. Still, Trump does not want to see Ukraine collapse on his watch. And Trump's relations with Vladimir Putin might deteriorate sharply if the Russian president does not accept Trump's conflict resolution efforts. European policymakers should increase their countries' defense expenditures in order to encourage the US to maintain its commitment to NATO. But European policymakers should also intensify planning for an independent European defense in case the American commitment falters European policymakers should do more to point out to their American counterparts that the Western competition with China is not just taking place in Asia, but worldwide - including in Europe.
Keywords: 330